2018
DOI: 10.14719/pst.2018.5.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and in vitro evaluation of alpha amylase, alpha glucosidase and beta galactosidase inhibition by aqueous and organic Atractylis gummifera L. extracts

Abstract: Diabetes is a chronic condition which is increasingly progressing throughout the world. To treat it, several methods are used, among which is medicinal plants that still have an unknown mechanism of action. The objective of this work is to evaluate the in vitro hypoglycemic effect of the extracts of the underground part of Atractylis gummifera, a member of Asteraceae used in traditional Moroccan medicine. A phytochemical study of the aqueous extracts (decocted, infused and macerated) and organic extracts (meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 0 publications
4
32
0
Order By: Relevance
“…Also, results showed that aqueous macerated of A. gummifera can significantly (p<0.05) reduce blood glucose in diabetic mice, which it's presumably due to reducing the damage of streptozotocin to pancreatic β-cells and enhancing the secretion of insulin (Wang et al, 2018). Also this decrease in blood sugar can be attributed to the richness of this extract in phenolic compounds (polyphenols and flavonoids) and in tannins (Bouabid et al, 2018) which are known for their ability to increase insulin sensitivity by the users' organs (liver, adipose tissue, muscle) and/ or inhibit the polysaccharide degradation process Asgharpour et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Also, results showed that aqueous macerated of A. gummifera can significantly (p<0.05) reduce blood glucose in diabetic mice, which it's presumably due to reducing the damage of streptozotocin to pancreatic β-cells and enhancing the secretion of insulin (Wang et al, 2018). Also this decrease in blood sugar can be attributed to the richness of this extract in phenolic compounds (polyphenols and flavonoids) and in tannins (Bouabid et al, 2018) which are known for their ability to increase insulin sensitivity by the users' organs (liver, adipose tissue, muscle) and/ or inhibit the polysaccharide degradation process Asgharpour et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
“…Besides, this extract has a very important role in inhibiting the enzymes responsible for the degradation of polysaccharides that has been demonstrated in vitro (Bouabid et al, 2018). Indeed, phytochemical screening revealed that the aqueous macerate of A. gummifera is an extract that contains tannins and flavonoids (Bouabid et al, 2018). Hence, molecular synergy has a beneficial effect in this case, which explains the action of this extract on several biochemical parameters and the restoration of their values back to normal.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations